Financial Performance Analysis of Agribusiness Microfinance Institutions in the Albarokah Farmers’ Group at Ketapang Village, Susukan, Semarang - Fariastuti, Mefi Fariastuti; Ekowati, Titik; Prastiwi, Wahyu Dyah (JURNAL LITBANG PROVINSI JAWA TENGAH, 2023)
The success measurement of a financial institution can be seen from the number of its members necessity are being met and its financial performance. One of the problems that makes it difficult for cooperatives to develop is financial management. The research aimed to 1). To find out the role of the Gardu Tani Multi-stakeholder Cooperative in helping farmers to access their farming needs, 2). Compare the financial performance of the Gardu Tani Multi-stakeholder Cooperative before and during the Covid-19 pandemic. The research was conducted in January – February 2022 at the Gardu Tani Multi-stakeholder Cooperative. The survey method is research carried out using questionnaires as a research tool taken from samples in a population. The data used is primary data obtained from interviews with respondents and secondary data obtained from books, journals and previous reports. Data were analysed using financial ratio analysis. Independent sample t test was conducted to test the hypothesis of the second research goals. The results are based first object showed that the role of the Gardu Tani Multi-stakeholder Cooperative in helping farmers are as followed: as a provider of production inputs; provider of agricultural equipment; provider of agricultural information, financing farming business, marketer, and promotion agent as well as money saving activities. Financial performance based on liquidity and solvency ratios were found in good criteria. Meanwhile, rentability ratios were found in poor criteria. The results of the independent sample t test on the current ratio, solvability ratios and rentability ratios showed there are no differences in financial performance before and during the Covid-19 pandemic. Furthermore, the result of the Mann-Whitney test on the quick ratio also found there are no differences in financial performance before and during the Covid-19 pandemic